Zintegrowane zarządzanie jakością usług turystycznych w regionach - Majcher, Patrycja (Integrated Tourism Services Quality Management in Regions, 2005)
In this article there is presented quality and tourism region questions. There is an attempt of showing meaning of co-operation between tourism organizations, unions or associations. There are also shown advantages of this kind of co-operations. Leadership has got also big role in integrated tourism management. A local government and inhabitants should also give support to tourism development, especially in good organization and using of region resources. There is also underlined public and private partnership in tourism services quality management on province, regional and local area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 124-130